Boganmeldelser - Dan Frände; Hans Henrik Brydensholt; Christian Diesen; Raimo Lahti; lnkeri Anttila; Mette-Lise Houman; Anette Storgaard; Peter Gottlieb; Gorm Toftegaard Nielsen; Birgitte Vestberg; Margaretha Järvinen; Ruth Nielsen; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé